Improved corrosion resistance of additively processed zirconium alloys

JP7637637B2Active Publication Date: 2025-02-28WESTINGHOUSE ELECTRIC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021564621
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-30
Filing Date
2020-04-23
Publication Date
2025-02-28
Estimated Expiration
2040-04-23

Smart Images

  • Figure 0007637637000009
    Figure 0007637637000009
  • Figure 0007637637000010
    Figure 0007637637000010
  • Figure 0007637637000011
    Figure 0007637637000011
Patent Text Reader

Abstract

A method is disclosed that includes forming a metal alloy component having a pre-specified three-dimensional geometry for use in a nuclear reactor by an additive manufacturing process followed by annealing at a first annealing temperature within an α-temperature range of a phase diagram for the metal alloy. A second annealing step at a second annealing temperature lower than the first annealing temperature may be added.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (cross reference) This application claims priority to U.S. Provisional Patent Application No. 62 / 841,067, filed April 30, 2019, the contents of which are incorporated herein by reference.

[0002] The present invention relates to additive manufacturing processes for producing parts for use in nuclear reactors, and more particularly to methods that include annealing the part following additive manufacturing. [Background technology]

[0003] Additive manufacturing (AM) (i.e., 3D printing) is a technology for realizing novel designs and complex geometries that cannot be easily produced using traditional manufacturing methods. In 2010, the American Society for Testing and Materials (ASTM) classified AM processes into seven categories in a new standard, "ASTM F42-Additive Manufacturing." The current categories of additive manufacturing processes are powder bed fusion, vat photopolymerization, binder injection, material extrusion, directed energy deposition, material jetting, and sheet lamination. These seven additive manufacturing processes contain notable variations of the layered 3D printing concept. The material state (powder, liquid, filament), heat or light source (laser, thermal, electron beam, plasma arc), number of printing axes, feeding system, and build chamber characteristics are all different.

[0004] Although additive manufacturing techniques have the ability to generate unique geometries that offer substantial performance advantages, there are challenges that prevent the nuclear industry from fully utilizing these unique additive manufacturing capabilities. For example, there is limited, if any, data available on the effects of neutron irradiation exposure on additively manufactured zirconium material properties. Summary of the Invention

[0005] The following summary is provided to facilitate an understanding of some of the innovative features unique to the disclosed embodiments and is not intended to be a complete description, A complete understanding of the various aspects of the embodiments can be obtained by taking the entire specification, claims, and abstract as a whole.

[0006] In one general aspect, the disclosure provides a method for additively manufacturing a component for use in a nuclear reactor. The method includes utilizing a feedstock that includes a metal to additively manufacture a component for use in a nuclear reactor. The method includes annealing the additively manufactured component at a first annealing temperature within an alpha phase temperature range of the metal, an alpha + beta phase temperature range of the metal, or a combination thereof.

[0007] In another general aspect, the present disclosure provides a method for additively manufacturing a part for use in a nuclear reactor. The method includes depositing a layer of powder feedstock including a zirconium alloy across a build plate, where at least selected regions of the layer are fastened together in selected regions. The fastening includes rastering a laser across the layer of powder feedstock along a path guided by a pre-entered computer-aided design file of the specifications of the three-dimensional component to be built, fusing the powder feedstock in the layer with the laser, and solidifying the molten powder. The deposition and fastening are repeated to provide an additively manufactured part. The additively manufactured component is removed from the build plate. The additively manufactured part is annealed at an annealing temperature within an alpha phase temperature range of the metal, an alpha-beta phase temperature range of the metal, or a combination thereof. [Brief description of the drawings]

[0008] The features and advantages of the present disclosure may be better understood with reference to the accompanying drawings.

[0009] [Figure 1A-1D]FIG. 13 is a representative image of the Zircaloy-2 powder used to print blocks additively manufactured by laser powder bed fusion. Note that both spherical and angular particles make up the powder geometry. The image is courtesy of ATI Specialty Alloys and Components, the source of the powder used in the experiments described herein.

[0010] [Figure 2A] FIG. 2A is a diagram showing the upper surface during the build-up process.

[0011] [Figure 2B] FIG. 2B shows the Zircaloy-2 block (B, right image) fabricated to its final mounting position on the build plate.

[0012] [Diagram 3] FIG. 1 illustrates one embodiment of a spacer grid formed from grid straps welded together, as shown in the inset.

[0013] [Figure 4A-4C] 4A-4C are optical micrographs of as-polished sections of additively manufactured Zircaloy-2 in three different orthogonal orientations. The build direction is along the Z axis.

[0014] [Figure 5A-5C] 13A-13C are SEM micrographs of irregularly shaped and spherical voids in additively manufactured Zircaloy-2.

[0015] [Figure 6A-6B] 6A-6B are optical micrographs of additively manufactured Zircaloy-2 microstructures.

[0016] [Figure 6C-6D] 6C-6D are SEM micrographs of additively manufactured Zircaloy-2 microstructures.

[0017] [Figure 7A] 13 is a cross-sectional SEM micrograph of an irradiated quad of additively manufactured Zircaloy-2, including oxide layers and hydrides, after irradiation at 0.9 dpa.

[0018] [Figure 7B] FIG. 7B is an SEM micrograph of a cross section of an irradiated quad of additively manufactured Zircaloy-2, including an oxide layer and hydrides, after irradiation at 1.6 dpa.

[0019] [Figure 8A] FIG. 8A is a polarized optical micrograph of an additively prepared Zircaloy-2 sample polished under polarized light but without annealing.

[0020] [Figure 8B] 1 is an optical polarizing micrograph of an additively manufactured Zircaloy-2 sample that has been polished but without annealing under polarized light.

[0021] [Figure 9A] 1 is a polarized light micrograph of an additively produced Zircaloy-2 sample after annealing at 760° C. for 2 hours.

[0022] [Figure 9B] 1 is a polarized light micrograph of an additively produced Zircaloy-2 sample after annealing at 760° C. for 2 hours.

[0023] [Figure 10] Phase diagram for the binary system Fe-Zr published in Handbook of Metals, vol. 8: Metallography, Structures and Phase Diagrams, American Society for Metals, Metals Park, OH 1973.

[0024] [Figure 11]Phase diagram for the binary system Sn-Zr published in Handbook of Metals, vol. 8: Metallography, Structures and Phase Diagrams, American Society for Metals, Metals Park, OH 1973.

[0025] [Figure 12] Phase diagram for the binary system Cr-Zr, published in Handbook of Metals, vol. 8: Metallography, Structures and Phase Diagrams, American Society for Metals, Metals Park, OH 1973.

[0026] [Figure 13A] FIG. 1 is a diagram of the measured poles of additively manufactured Zircaloy-2 material.

[0027] [Figure 13B] FIG. 1 is a calculated polar diagram of additively manufactured Zircaloy-2 material.

[0028] [Figure 14A] 1 is a scanning electron micrograph of the oxide layer formed on an autoclave corrosion sample of as-prepared additively manufactured Zircaloy-2 after exposure to 427° C. steam for 9 days.

[0029] [Figure 14B] FIG. 1 is a scanning electron micrograph of the oxide layer formed on an autoclave corrosion sample of additively manufactured Zircaloy-2, including exposure to water vapor at 427°C for 9 days, followed by a 2-hour anneal at 760°C.

[0030] [Figure 15A] 1 is a SEM micrograph of a fracture surface of a tensile room temperature (RT) test sample of non-irradiated, fully recrystallized (RXA) Zircaloy-2.

[0031] [Figure 15B] 1 is a SEM micrograph of the fracture surface of a non-irradiated AM Zircaloy-2 tensile RT test sample.

[0032] [Figure 15C] 1 is a SEM micrograph of the fracture surface of a non-irradiated, fully recrystallized (RXA) Zircaloy-2 tensile 573°K test sample.

[0033] 15D is an SEM micrograph of the fracture surface of a non-irradiated AM Zircaloy-2 tensile 573°K test sample.

[0034] [Figure 16A] 13 is an SEM micrograph of the fracture surface of a tensile RT test specimen of an irradiated 0.9 dpa AM Zircaloy-2 sample.

[0035] [Figure 16B] 13 is an SEM micrograph of the fracture surface of an irradiated 1.6 dpa AM Zircaloy-2 tensile RT test sample.

[0036] [Figure 16C] 1 is an SEM micrograph of the fracture surface of an irradiated 0.9 dpa AM Zircaloy-2 tensile 573°K test sample.

[0037] [Figure 16D] 1 is an SEM micrograph of the fracture surface of an irradiated 1.6 dpa AM Zircaloy-2 tensile 573°K test sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] As used herein, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, the articles "a" and "an" are used herein to refer to one or to more than one (i.e., to at least one) of the grammatical objects of the article. For example, "an element" means one or more elements.

[0039] In this application, including the claims, unless otherwise indicated, all numbers expressing quantities, values, or properties should be understood in all instances to be modified by the term "about", and thus, even if the term "about" is not explicitly expressed in the number, the number can be read as if it were preceded by the term "about". Thus, unless indicated to the contrary, any numerical parameter set forth in the following description may vary depending on the desired properties sought to be obtained in the compositions and methods according to the present disclosure. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter set forth herein should be construed at least in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0040] Furthermore, any numerical range recited herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include any and all subranges between (and including) the recited minimum value of 1 and the recited maximum value of 10, i.e., having a minimum value of 1 or more and a maximum value of 10 or less.

[0041] Nuclear reactor components benefit from the use of additive manufacturing processes, especially when material properties are improved to enhance corrosion resistance. It has been unexpectedly discovered that fully recrystallized alloys can be produced by applying a high temperature anneal after printing the part, when the temperature range of the anneal is within either the alpha or alpha + beta temperature range of the phase diagram for the selected metal. The high temperature anneal also nucleates and coarsens second phase particles (SPPs) in the alloy.

[0042] The present disclosure provides methods for additively manufacturing components for use in nuclear reactors (e.g., light water reactors or small modular reactors), where the components may be fully recrystallized and / or have improved corrosion resistance. The components may include debris filters, mid-flow mixers, or spacer grids, or combinations thereof. Components manufactured according to the present disclosure may include improved heat transfer and thermal-hydraulic performance.

[0043] The method includes additively manufacturing a component for use in a nuclear reactor utilizing a feedstock including a metal including a zirconium alloy. The feedstock can include a powder, a sheet, or a wire, or a combination thereof. In an embodiment where the feedstock includes a powder, the powder feedstock can include an average particle size ranging from 10 micrometers to 100 micrometers, for example, 40 micrometers to 80 micrometers. The particle size can be measured by scanning electron microscopy, transmission electron microscopy, sieve screens, or laser diffraction. It is contemplated that smaller or larger particle sizes may also be used. The additive manufacturing process can include powder bed fusion, vat photopolymerization, binder jetting, material extrusion, directed energy deposition, material jetting, or sheet lamination, or a combination thereof.

[0044] The metal can include a zirconium alloy. For example, the metal can include Zircaloy-2, Zircaloy-4, HiFi™, binary zirconium alloys, and non-binary zirconium alloys including tin and another alloying element, ZIRLO, ZIRLO Optimized, AXIOM, non-binary zirconium alloys including niobium and another alloying element, or combinations thereof. In some examples, the zirconium alloy can include niobium, such as binary zirconium alloys including niobium (e.g., Zr-1Nb, Zr-2.5Nb, M5, E110), or non-binary zirconium alloys including niobium and another alloying element. Various zirconium alloys can be used in nuclear reactor applications due to the low neutron cross section, relatively good corrosion resistance, and desirable mechanical properties of various zirconium alloys.

[0045] Additive manufacturing can include generating a computer-aided design (CAD) file for a desired component geometry, inputting the CAD file into an additive manufacturing system, and introducing a desired feedstock into the additive manufacturing system. In an example where additive manufacturing includes powder bed fusion with a laser, additive manufacturing can include depositing a layer of powder feedstock including a metal across a build plate of the additive manufacturing system. At least selected regions of the layer can be fixed together in selected regions utilizing a laser of the additive manufacturing system. For example, a laser can be rastered across the layer of powder feedstock along a path guided by a computer-aided design file for the three-dimensional component to be built. The computer-aided design file can be input into a computer controlling the additive manufacturing system prior to the start of the component build process. The powder feedstock within the layer can be melted by the laser.

[0046] The laser can then be removed from selected areas of the layer, allowing the molten powder to solidify. The deposition of powder feedstock and fixing with the laser can be repeated to provide an additively manufactured part. The additively manufactured component can then be annealed for a period of time at a first annealing temperature in the alpha phase temperature range, or the alpha + beta phase temperature range of the metal, or a combination thereof.

[0047] In various examples, the annealed additively manufactured part can be annealed at a second annealing temperature for a second time. For example, the additively manufactured component can be heated to a first annealing temperature for a first time, reduced to a second temperature, and held at the second temperature for a second time. After the second time and any subsequent times, the temperature is reduced to room temperature to complete the annealing.

[0048] In various examples, a first annealing temperature may be in the alpha phase temperature range of the metal, which can facilitate recrystallization of the microstructure, followed by an optional second annealing temperature also in the alpha phase temperature range of the metal, but at a lower temperature to limit grain growth. This approach can provide flexibility in tailoring the appropriate anneal for additively manufactured components. In another example, the first anneal temperature can be in the alpha + beta temperature range of the metal, which can facilitate microstructural recrystallization, and the second anneal temperature can be in the alpha temperature range of the metal, which can improve the size and distribution of second phase particles. For example, an anneal in the alpha + beta temperature range followed by an anneal in the alpha temperature range can be beneficial for zirconium alloys containing niobium.

[0049] In various examples, the first annealing temperature can be within the alpha phase temperature range of the metal, and the second annealing temperature can be within the alpha + beta phase temperature range of the metal. The second annealing temperature can be lower than the first annealing temperature. For example, the first annealing temperature can be in the range of 450°C to 800°C, such as, for example, 600°C to 800°C, 700°C to 800°C, 740°C to 780°C, 450°C to 600°C, 530°C to 580°C, or 450°C to 620°C. In various examples, the initial annealing temperature is 760°C. The second annealing temperature can be in the range of 450°C to 620°C, such as, for example, 530°C to 580°C or 450°C to 600°C. The annealing can recrystallize the microstructure of the part so that the additively manufactured part is suitable for use in a nuclear reactor. In various examples where the metal includes a niobium alloy with zirconium, the first annealing temperature can be in the range of 600°C to 800°C and the second annealing temperature can be in the range of 450°C to 600°C, 450°C to 620°C, or 530°C to 580°C. In various examples, the first annealing temperature and first duration can promote recrystallization and the second annealing temperature and second duration can enable SPPs of desired composition and size distribution for the core component. For example, the metal can include an alloy including a matrix of a first phase metal and a second phase metal and the second annealing temperature achieves a desired composition and size distribution for the second phase metal. In an example where the metal comprises a zirconium alloy with niobium, the second annealing temperature and second time can ensure that β-zirconium is converted to β-niobium (and α-zirconium), thereby improving corrosion properties (increasing resistance to oxidation and hydrogen pick-up).

[0050] The additively manufactured part can be annealed for a total time period ranging from 0.1 hours to 100 hours, such as, for example, from 0.1 hours to 10 hours or from 1 hour to 3 hours. For example, the first time period can range from 0.1 hours to 100 hours, such as, for example, from 0.1 hours to 10 hours or from 1 hour to 3 hours. In some examples, the first time period can be 2 hours.

[0051] Electron beam melting is one example of an additive manufacturing technique that can create metal parts. The method uses a metal powder that is melted by an electron beam. The powder is typically melted in a vacuum to form a three-dimensional shape, layer by layer. Another type of additive manufacturing uses a laser to melt the metal into the desired three-dimensional shape. This technique typically involves using a laser to heat the metal into a molten pool, after which more metal is added, layer by layer. The laser again moves across either the powder bed or the surface of the part as new material is added, thereby producing the desired object.

[0052] Zirconium alloys may contain primary metals that form a matrix phase with second phase particles dispersed throughout the matrix. Before obtaining the finished product, several thermomechanical processing steps may be performed during which recrystallization occurs and second phase particles (SPPs) nucleate and coarsen. The second phase particles may delay or accelerate recrystallization depending on factors such as particle size and spatial distribution, and processing conditions. Furthermore, the SPP size distribution may affect the corrosion and hydrogen pickup resistance of the final product. Since the microstructure of additively manufactured materials can be significantly different from conventionally processed materials in terms of grain size and shape, texture, precipitate type and composition, and precipitate size distribution, the irradiation response of additively manufactured parts of alloys commonly used in nuclear reactors may have to be directly tested to determine whether the additively manufactured materials behave differently from current conventional materials.

[0053] Zirconium alloys are traditionally used in various components of nuclear reactors. The typical composition of nuclear grade zirconium alloys is greater than 95% by weight zirconium, with typically less than 3% by weight of one or more of tin, niobium, iron, chromium, nickel, and other metals added to improve mechanical properties and corrosion resistance. For example, the zirconium alloys known as Zircaloy-2 and Zircaloy-4 contain approximately 98% by weight zirconium and 1.2-1.7% by weight tin, as well as smaller amounts of chromium and iron, but no niobium. Zircaloy-2 and HiFiTM also contain nickel. HiFiTM is another alloy like Zircaloy-2 that contains a higher concentration of iron (0.4% by weight). Zirconium alloys sold under the trade names ZIRLO and ZIRLO Optimized™ have approximately 0.6-1.1 wt% tin, 0.8-1.2 wt% niobium, and 0.09-0.13 wt% iron, with the remainder being zirconium. AXIOM® is another zirconium-based alloy containing small amounts of niobium, tin, iron, copper, and vanadium. The nominal ranges for AXIOM® are 0.7-1.0 wt% Nb, 0.3-0.4 wt% Sn, 0.05-0.1 wt% Fe, 0.1-0.2 wt% Cu, and 0.2-0.3 wt% V, while Zircaloy-4, ZIRLO®, and AXIOM® alloys are nickel-free. One of the challenges for using zirconium materials in nuclear applications is to achieve acceptable corrosion behavior while maintaining sufficiently good mechanical properties.

[0054] Due to the rapid cooling of the molten pool and metal powders used during various additive manufacturing processes, the alloying additives may remain in solution or form very fine second phase particles. Both conditions can be detrimental to in-reactor corrosion, and additive manufacturing process methodologies may not produce microstructures optimized for corrosion resistance.

[0055] Conventional processing of zirconium-based alloys may typically involve multiple iterations of beta-forging an ingot, beta-quenching, hot treating, alpha-annealing to final dimensions, and cold treating, followed by a final anneal [1].

[0056] As used herein, "beta quench" is the process of cooling from the beta phase (body-centered cubic crystal structure). The transformation from beta to alpha results in a lathe type structure, and lathe to alpha (hexagonal close-packed crystal structure). At high cooling rates (greater than 500°C per second), the alpha phase becomes slightly distorted and is commonly referred to as martensite.

[0057] Annealing is a heat treatment that changes the physical, and sometimes chemical, properties of a material in order to increase its ductility and decrease its hardness, making it easier to work with. In a typical annealing process, a material is heated above its recrystallization temperature, held at or near that temperature for a period of time, and then cooled.

[0058] Additive manufacturing is a significant departure from traditional processing. Unlike traditional processing, additive manufacturing can produce final size parts directly from the starting material. Although other additive manufacturing methods may be used, laser powder bed fusion (LPBF) can be used when the starting material is a powder. The laser melts the powder locally, resulting in a beta-quenched microstructure upon cooling from the melt. An advantage of additive manufacturing can be the ability to produce final size components with complex geometric shapes. However, this advantage can prevent further mechanical processing of the part and limit post-additive manufacturing processing to heat treatment.

[0059] The design of nuclear reactor components is limited by conventional manufacturing techniques. As an example, spacer grids can typically be manufactured by welding stamped grid straps together to form a grid that becomes part of a nuclear fuel rod assembly, as shown in the inset of Figure 3. In order to additively manufacture any such components, the material properties of the resulting part need to be comparable or better than those of materials resulting from conventional processes. The processes described herein can improve the performance of additively printed zirconium alloy materials enough to make additive manufacturing of such components acceptable. In today's standard processing, multiple cycles of alpha annealing and cold working to final size followed by a final annealing can provide a favorable texture in the final product. One feature of additively manufactured Zr-based alloys can be a randomized final crystal structure that reduces irradiation-induced growth in the components.

[0060] The inventors have found that a fully recrystallized microstructure following high temperature alpha annealing of additively manufactured Zircaloy-2 material according to the methods herein can be advantageous. Although this anneal can be performed to nucleate and roughen second phase particles, an unexpected result was a complete recrystallization of the material. Typically, beta annealed zirconium alloys do not recrystallize during the subsequent alpha anneal. However, we believe that recrystallization occurs due to the quenching strain in the additively manufactured material and the high annealing temperature (e.g., 750°C). In preliminary testing, the additively manufactured material exhibited similar corrosion properties to conventional Zircaloy-2. Based on the presence of random texture in the printed additively manufactured material, it is expected that the texture of the annealed additively manufactured material will be random, resulting in lower in-reactor irradiation induced growth.

[0061] The processes described herein can produce unique geometries that can improve the performance of fuel assemblies used in nuclear reactors. The processes described herein can enable alternative designs and manufacturing methods for reactor components, such as fuel assembly lattice designs that can enhance the thermal-hydraulic performance of the fuel assemblies.

[0062] Another challenge for additive manufacturing of parts for use in nuclear reactors, for example zirconium alloys, can be to achieve acceptable corrosion behavior from 3D printing alone.

[0063] There may be limited opportunity to achieve a microstructure optimized for corrosion alone. However, annealing the material can create a fully recrystallized microstructure for alloys previously shown to be corrosion resistant in the high temperature α region as shown in the phase diagram of the selected alloys that nucleates and coarsens second phase particles (SPPs) after printing. Coarsening the second phase particles addresses issues from having very fine SPP sizes, which have been found to be detrimental to in-reactor corrosion performance. As used herein, "very fine" means below 40 nanometers. Zircaloy-2 alloys have too few grains below 40 nm. Particles of this size dissolve in Zircaloy-2 when irradiated, compromising corrosion resistance.

[0064] A phase is the crystal structure of a metal at a given temperature range. The alpha range is below 815°C for Zircaloy-2 (see Figures 10-12). This temperature can be raised or lowered depending on any alloying additions or impurities. These additions can form small regions rich in an element within the zirconium microstructure. Typically, these regions can form fine grains in the material. Grain is a microstructural feature that affects the performance of a metal or material. Boundaries are interfaces between two or more grains. Particles called second phase particles can appear as small dots in a micrograph between larger blocky grains. Impurities or alloying additions can help nucleate second phase particles.

[0065] A desirable microstructure may be one that has grains that are similar in size and equiaxed (i.e., no longer in one particular direction). Zirconium alloys typically tend toward small grain size (~ASTM grain size 10 or less), and to achieve this, multiple steps of cold working (e.g., pilering or rolling for Zr alloys) and annealing may be performed. This multi-step process may be followed for conventionally processed zirconium alloys. This process can help break down the as-cast structure.

[0066] An alpha anneal at 760°C for 2 hours was applied to the additively manufactured Zircaloy-2 material, and then the samples were tested in a short-term steam autoclave (427°C / 1500 psi, 9 days). The weight gain after the short-term autoclave test was measured, and the gain was comparable to the conventional Zircaloy-2 material, as shown in Table 1 below. The samples were then metallographically tested and shown to result in a fully recrystallized microstructure (Figures 9A and 9B). The resulting microstructure brings the additively manufactured Zr material closer to conventionally processed materials; a more desirable microstructure, but a geometry not easily achieved by conventional machining techniques. Traditionally, zirconium will not recrystallize without cold work based on stresses placed in the material. In additively manufactured materials, it is hypothesized that the necessary stresses result from rapid quenching during additively manufactured manufacturing. Additionally, the recrystallized microstructure is expected to have a random texture that can minimize in-reactor irradiation growth.

[0067] In various embodiments, additive manufacturing may be applied to other zirconium-based alloy compositions. For example, Zr-Nb-based alloys are another class of alloys that would benefit from processes to obtain acceptable corrosion properties within additive manufacturing. Zr-Nb second phase particles (β-Nb) behave differently under irradiation than second phase particles in Zircaloy. Beta-niobium particles are generally smaller (~20 nm in size) than SPPs in Zircaloy and are more resistant to radiation-induced amorphization and dissolution.

[0068] Preferred annealing temperatures for use in the process may range from 450 to 800°C for Zircaloys (Zircaloy-2 and Zircaloy-4 based alloys) and 450 to 620°C for Zr-based alloys such as binary Zr-Nb alloys, ZIRLO, optimized ZIRLO, AXIOM, and other alloys that contain Nb and lower the α to α + β phase transformation temperature.

[0069] The preferred annealing temperatures for additively manufactured materials are in the alpha range and high, preferably in the alpha range, where the range depends on the alloy. See (Tong, VS and TB Britton, "formation of very large 'blocky alpha' grains in Zircaloy-4", Acta Materialia, 129 (2017) 510-520; and DFWashburn, "the formation of large grains in alpha Zircaloy-4 during heat treatment after small plastic deformations, " Knolls Atomic Power Laboratory, General Electric Company, Report KAPL-3062, New York, 1964) where recrystallization following low amounts of deformation is shown to have occurred only high in alpha temperature range. example [Table 1]

[0070] In the first set of experiments, a commercial industrial 3D printer was used to produce blocks of additively manufactured material by laser powder bed fusion, with the starting material being Zircaloy-2 powder. The goals of the study were to demonstrate: Near theoretical density was achieved in Zircaloy-2 material additively produced from the starting powder. There were no significant chemical changes between the starting powder and the resulting block. Potential concerns were depletion of alloying elements and pick-up of oxygen and nitrogen during laser melting of the powder. Acceptable mechanical properties were maintained in the as-fabricated and additively fabricated condition as well as after short-term irradiation (up to 1.6 dpa). The corrosion behavior of as-additively manufactured materials was evaluated and options for corrosion improvement were identified.

[0071] The results of this preliminary evaluation of additively manufactured zirconium alloys are presented below, along with an assessment of the technical challenges that need to be resolved prior to the application of additive manufacturing for light water reactor zirconium alloy components.

[0072] experiment Laser Powder Bed Fusion

[0073] Laser powder bed fusion (LPBF) is an additive manufacturing production technique that uses a laser to melt and fuse powder. Zirconium is a highly reactive metal in its molten state, and its powder is pyrophoric, so an inert atmosphere or high vacuum system is required for safety [2]. A thin layer of power is spread across the build plate, and the laser is rastered across the plate as the specifications of a previously built three-dimensional (3D) part are guided by a computer-aided design (CAD) file. The powder melts under the laser power and rapidly solidifies [2]. Then, another layer of fresh powder is dispensed across the freshly built layer, and the process is repeated in the build chamber. This layer-by-layer deposition is built up in the z-axis direction until the 3D component is complete. Loose, unbonded material is then removed from the component, and the part is detached from the build plate.

[0074] ZIRCALOY-2 Material Powder

[0075] Blocks of additively manufactured Zircaloy-2 were produced by laser powder bed fusion (LPBF) using an EOS industrial 3D metal printer (model EOS M280). Zircaloy-2 powder was selected as the source material for 3D printing as it is readily available from ATI Specialty Alloys & Parts. The powder was first produced by a hydride / dehydride (HDH) process and sieved to control particle size. The sieved powder was then subjected to a plasma spheroidization treatment to achieve the desired shape and flow properties for printing. Many of the particles were made spherical, but angular particles still remained. Images of the powder are shown in Figures 1A-1D. The powder size ranged from 40-60 micrometers and the powder chemistry is reported in Table 2. [Table 2]

[0076] Additively manufactured building blocks

[0077] The additively manufactured block geometry is shown in Figure 2B with nominal dimensions in the XY plane of 100 mm × 78 mm. The height of the block (Z plane, or build direction) was approximately 50 mm. The block was formed by laser melting successive thin layers (40 micrometers) of Zircaloy-2 powder as shown in Figure 2A. Due to the printing process used, the X and Y directions were expected to be essentially identical in terms of microstructure and mechanical properties. Printing parameters were developed to provide an optimal concentration of built structures, and selected details are provided in Table 3. The chemistry of the as-printed block is shown in Table 2 along with the ASTM elemental ranges for Zircaloy-2 alloy [6]. Samples for characterization were cut from the block by electrical discharge machining (EDM). [Table 3]

[0078] Conventional Plate

[0079] Two 3.4 mm thick plates of recrystallized Zircaloy-2 were purchased from ATI Specialty Metals Inc. and used as comparative material. The chemical composition of the plates was similar to that of the powder and is reported in Table 2.

[0080] Various aspects of specific non-limiting embodiments of the invention encompassed by this disclosure include, but are not limited to, those recited in the following numbered paragraphs. 1. A method for additively manufacturing a component for use in a nuclear reactor, the method comprising: A component for use in a nuclear reactor is additively manufactured utilizing a feedstock comprising a metal, and the additively manufactured component is annealed at a first annealing temperature within an alpha phase temperature range, an alpha+beta phase temperature range of the metal, or a combination thereof. 2. The method of claim 1, wherein the first annealing temperature is within an alpha phase temperature range of the metal, and the method further comprises annealing the additively manufactured component for a second time at a second annealing temperature within the alpha + beta phase temperature range of the metal. 3. The method of any one of paragraphs 1 to 2, wherein the metal comprises a zirconium alloy. 4. The method of any one of paragraphs 1 to 3, wherein the metal comprises Zircaloy-2, Zircaloy-4, HiFi™, a binary zirconium alloy, or a non-binary zirconium alloy containing tin and another alloying element, or a combination thereof. 5. The method of any one of paragraphs 1 to 3, wherein the metal comprises ZIRLO, optimized ZIRLO, AXIOM, a binary zirconium alloy containing niobium, or a non-binary zirconium alloy containing niobium and another alloying element, or a combination thereof. 6. The method of any one of clauses 1 to 5, further comprising annealing the additionally manufactured part for a second time at a second annealing temperature lower than the first annealing temperature. 7. The method of any one of paragraphs 1 to 6, wherein the feedstock comprises a powder, a sheet, or a wire, or a combination thereof. 8. The method of any one of clauses 1 to 3 and 5 to 7, wherein the metal comprises a zirconium alloy containing niobium, the first annealing temperature is in the range of 600°C to 800°C, and the second annealing temperature is in the range of 450°C to 600°C. 9. The method according to item 8, wherein the second annealing temperature is in the range of 530°C to 580°C. 10. The method of any one of claims 1 to 9, wherein the first annealing temperature recrystallizes the microstructure of the additively manufactured part. 11. The method of claim 10, wherein the metal comprises an alloy including a matrix of a primary phase metal and a secondary phase metal, and the second annealing temperature achieves a composition and size distribution of the dual-phase metal suitable for use in a nuclear reactor. 12. The method of any one of claims 1 to 11, wherein the additive manufacturing process comprises powder bed fusion, vat photopolymerization, binder jetting, material extrusion, directed energy deposition, material jetting, or sheet lamination, or a combination thereof. 13. A method of additively manufacturing a part for use in a nuclear reactor comprising: depositing a layer of powder feedstock comprising a zirconium alloy across a build plate; clamping at least selected areas of the layers together in selected areas, the clamping including: rastering a laser across the layer of powder feedstock along a path guided by a pre-entered computer aided design file of specifications for a three dimensional part to be built; melting the powder feedstock in the layer with a laser; solidifying the powder feedstock; repeating the deposition and clamping to provide an additively manufactured part; removing the additively manufactured part from the build plate; and annealing the additively manufactured part at an annealing temperature within an alpha phase temperature range of the metal, an alpha-beta phase temperature range of the metal, or a combination thereof. 14. The method of claim 13, wherein the metal comprises Zircaloy-2, Zircaloy-4, HiFi™, a non-binary zirconium alloy containing tin and another alloying element, ZIRLO, ZIRLO Optimized, AXIOM, a binary zirconium alloy containing niobium, or a non-binary zirconium alloy containing niobium and another alloying element, or a combination thereof. 15. The method according to any one of items 13 to 14, wherein the annealing temperature is within the range of 450°C to 800°C. 16. The method according to any one of items 13 to 15, wherein the alloy comprises a zirconium alloy containing niobium, and the annealing temperature is within the range of 450°C to 620°C. 17. The method according to any one of items 13 to 16, wherein the annealing is carried out for a time period ranging from 0.1 hours to 100 hours. 18. The method of any one of claims 13 to 17, wherein the component comprises a debris filter, an intermediate flow mixer, a spacer grid, or a combination thereof. 19. The method of any one of claims 13 to 18, wherein the powder feedstock comprises an average particle size in the range of 10 micrometers to 100 micrometers. 20. The method according to any one of items 13 to 15 and 17 to 19, wherein the annealing temperature is in the range of 740°C to 780°C, and the annealing is carried out for a time period in the range of 1 hour to 3 hours.

[0081] Conventional Zircaloy-2 plates manufactured by Sandvik were included in selected autoclave corrosion tests (described below). One type was treated under recrystallization conditions, and the other was beta-quenched (BQ) after recrystallization. Beta-quenching was performed to randomize the texture to minimize dimensional changes due to irradiation growth. The chemistry of the fully recrystallized (RXA) and BQ / RXA plates is reported in Table 2. Further details are disclosed in Dahlback, M., et al., "The Effect of Beta-Quenching in Final Dimension on Irradiation Growth of Tubes and Channels" Zirconium in Nuclear Industry: Fourteenth International Symposium, STP 1467, B Kammenzind and P. Rudling Eds., ASTM International, West Conshohocken, PA, 2005, pp. 276-304.

[0082] Characterization technology density

[0083] Immersed density measurements were performed using a Mettler Toledo XXP Precision balance with an immersed density kit containing deionized water. The balance was checked using NIST traceable calibration weights and the instrument's built-in density calculation software was checked using a pure titanium rod. Calculations were based on [5]. Measurements were performed on intact, non-irradiated quads. Ten wet and dry measurements were performed on each quad and the results were averaged.

[0084] Porosity measurements were also made on metallurgical mounts of cross-sectionally additively manufactured materials (see below). Porosity was measured digitally and percent theoretical density minus porosity equaled 100%.

[0085] crystal structure

[0086] The crystallographic texture of additively manufactured block specimens was measured by direct pole figure analysis [7]. The specimens were polished to remove the residual EDM layer and prepare a flat surface for the measurements. The pieces were then lightly pickled in a 45H2O-45HNO3:10HF solution and all the cold work introduced on the surface was polished away. The samples were analyzed.

[0087] The complete pole figures were obtained from the orientation distribution function (ODF). The ODF was calculated using the texture analysis software popLA [8,9]. Input to the program was data from the following partial pole figures:

number

[0088] Texture parameters for three orthogonal directions (normal, horizontal, vertical) were calculated from the complete pole figures. The calculated texture parameters were tabulated with respect to the base pole and renamed based on the three block directions X, Y, and Z, where Z is the build direction.

[0089] Microstructure

[0090] Specimens were selected for metallurgical mounting; optical optical microscopy (LOM) and scanning electron microscopy (SEM) evaluation. One sample from each direction (X, Y, and Z) was cross-sectioned for the non-irradiated additive manufactured material and the conventional ATI plate material.

[0091] In many cases, few features could be discerned in the unirradiated samples in the as-polished condition, so a light etch consisting of 45H2O:45HNO3:5HF was used to bring out the grain structure in the cross section. Swabbing was kept to 5-10 seconds to reduce pitting of the material.

[0092] Mechanical testing

[0093] microhardness

[0094] Microhardness measurements were performed on the as-polished surfaces on a Wilson Instruments Tukon 2100B testing machine

[10] . A Vickers indenter was used with a 50X objective lens, 500 grams force load and 10 seconds dwell time. Traces were made within the central area of ​​the mounted sample.

[0095] Corrosion Testing

[0096] Oxidation

[0097] Steam corrosion tests in an autoclave were carried out on selected unirradiated Zircaloy-2 specimens. Tests were performed at 427 °C and 10.3 MPa pressure according to ASTM G2

[13] . Samples were weighed after selected time intervals and the mass gain was calculated and recorded.

[0098] hydrogen

[0099] All hydrogen measurements were performed on a LECO RHEN 602 analyzer. Measurements were performed after short-term autoclave testing. All samples were washed with acetone and weighed prior to analysis.

[0100] result

[0101] Density and Chemistry

[0102] Initial evaluation of the Zircaloy-2 blocks included density and chemistry to confirm that additive manufacturing could produce a fully dense material without significant chemical changes from the starting powder.

[0103] The densities determined by both immersion and metallography are summarized in Table 5. Using an RXA Zircaloy-2 plate as a reference for 100% dense material, the immersion technique showed that the additively manufactured material was 99.9% dense. Metallography performed on the additively manufactured samples confirmed the high density. Polished sections from the gauge sections of the mini tensile specimens (see Figures 4A-4C) revealed an area fraction of voids of approximately 0.1%, corresponding to a density of 99.9%. The voids were isolated inside the specimens and consisted of both irregularly shaped holes due to incomplete melting of the powder or spherical voids from trapped gas, as shown in Figures 5A-C. [Table 5]

[0104] All of the major alloying additions (Sn, Fe, Cr, and Ni) remained well within the broad ASTM specifications for Zircaloy-2 [6]. The oxygen content of the powder was 1600 wPPM, higher than the more typical value of 1200 wPPM. Additionally, the nitrogen content of the powder was high, exceeding the ASTM maximum of 80 wPPM nitrogen. It is not known whether the high oxygen and nitrogen content of the powder is due to high values ​​in the starting materials used to make the powder or to pick up during the process of making the powder. Despite the high oxygen and nitrogen values ​​in the powder, the composition of the block showed only minor pickup of additional oxygen and no further pickup of nitrogen. It is noted that the hydrogen content in the block is higher than the ASTM maximum of 25 wPPM hydrogen, although there is no known source of high hydrogen.

[0105] Texture Crystallographic texture measurements revealed that the additively manufactured material was isotropic (see Figures 14A and 14B). The texture parameters in three orthogonal directions (X, Y, and Z) in Table 6 were close to 0.333 indicating a random texture. Included in the table for comparison are the texture parameters for a conventionally processed Zircaloy-2 plate manufactured by multiple iterations of rolling and annealing. The values ​​are representative of conventionally processed material and result from a hexagonal alpha phase crystal structure. [Table 6]

[0106] Microstructure

[0107] With Z as the build direction, low magnification optical micrographs of the additively produced block were taken in three orthogonal directions. Figures 4A and 4B are planes perpendicular to the X and Y directions, respectively. As can be seen in the micrographs, the large grains are elongated along the Z (build) direction. Looking down the Z axis, the grains become equiaxed, as shown in Figure 4C. This structure is the result of localized melting of each successive powder layer by the laser light.

[0108] Higher magnification optical and SEM images of additively manufactured Zircaloy-2 blocks are shown in Figures 6A-6D. They show a beta-quenched microstructure consisting of very fine (<1 μm) alpha phase lathes

[14] . The presence of solid Zircaloy-2 beneath each layer of Zircaloy-2 powder provides a heat sink for very rapid cooling as the melt solidifies as the beta phase and then transforms to the alpha phase. Microstructures with cooling rates from the beta phase greater than 500 K / s to 1000 K / s [15, 16], 16] are typically described as martensite. Although the cooling rates during additively manufactured builds of Zircaloy-2 blocks were not measured, the very fine microstructures were consistent with a martensitic structure.

[0109] mechanical properties microhardness

[0110] The Vickers microhardness results are shown in Table 7. The loading direction was perpendicular to the ground surface. [Table 7]

[0111] Conventional RXA materials exhibited differences in microhardness between the longitudinal and transverse directions. The average microhardness was slightly higher in the transverse orientation (188 HV) compared to the longitudinal orientation (170 HV). These differences are due to the crystallographic texture of the material. These values ​​are within the typical range for fully RXA zirconium materials.

[0112] The additively manufactured Zircaloy-2 quad had similar measurements in all three directions. The average microhardness in the three directions was 261 HV. The material is harder than the conventional material and is isotropic. After annealing at 760°C / 2 hours, the hardness of the AM Zircaloy-2 decreased significantly to 207, consistent with a recrystallization of the material.

[0113] Fractography

[0114] Comparative images between room temperature (RT) tensile fracture and high temperature fracture (573 K) are shown in Figures 15A-15D and 16A-16D. The conventional material was very ductile and many uniform void features were exhibited throughout the fracture surface (see Figures 15A and 15C). Large isolated pores were observed in the non-irradiated RT additively manufactured material that appeared to be uniformly distributed within the fracture surface (see Figure 15B). The pores ranged in size from 20 to 80 micrometers. Ductile regions were also seen on the fracture surface. More dimple-like ductile regions were present in the elevated tensile (see Figures 15C and 15D). Pores were also present in the high temperature additively manufactured tensile and were similar in size to those observed in the RT additively manufactured tensile (see Figure 15D).

[0115] The irradiated fracture surfaces were in stark contrast to the non-irradiated additively manufactured material (see Figures 16A and 16B). Pores were found, but were much smaller in diameter (less than 20 micrometers). Less reduction in area was observed in the irradiated samples with increasing dose. Ductile zones were observed at the periphery of the fracture surface for the high-temperature irradiated samples (see Figures 16C and 16D). Despite the reduction in elongation, additively manufactured Zircaloy-2 appears to retain the ability to locally deform in plastic regions rather than brittle fracture, consistent with what has been observed in conventional Zircaloy-2 materials

[18] .

[0116] corrosion

[0117] Optimizing the corrosion performance of additively manufactured materials was outside the scope of the initial exploratory study. However, limited efforts were made to evaluate the effect of annealing on corrosion. Additively manufactured coupons were prepared by grinding the surface on silicon carbide paper to remove the recast layer that was present by the electrical discharge machining process. Two coupons were annealed at 760 °C for 2 h to precipitate and coarsen second phase particles (SPPs). The two annealed coupons along with two as-milled coupons were cleaned and autoclave tested in 427 °C / 10.3 MPa steam.

[0118] Weight gain results from the autoclave testing are shown in Table 1, and oxide cross sections are shown in Figures 7A-7B. Oxide cross sections of both the printed column and the annealed additively manufactured material are shown in Figures 7A and 7B. Also included in Table 10 are weight gains from Zircaloy-2 plates produced by conventional processing, as well as Zircaloy-2 plates imparted by convection cooling. Because the EDM surfaces were removed from the autoclave specimens prior to testing, the autoclave results reflect the influence of the additively manufactured specimen microstructure. As previously mentioned, the additive manufacturing process produced a beta-quenched microstructure in the material following the rapid solidification of the localized melt pools produced by the laser beam. This anneal was intended to nucleate and coarsen the SPPs, but it also recrystallized the beta-quenched microstructure, as shown in Figures 7A and 7B. Annealing resulted in a significant reduction in oxidation in short-term water vapor tests, with weight gain decreasing from an average of 145 mg / dm2 to approximately 50 mg / dm2. Weight gain for the annealed samples was in the same range as conventionally treated material.

[0119] The hydrogen pick-up for the additively manufactured material normalized to a coupon thickness of 0.5 mm is also reported in Table 1 along with the pick-up normalized to a coupon thickness of 0.5 mm. The percent theoretical hydrogen pick-up was 24% for the additively manufactured material in both the as-manufactured and annealed conditions.

[0120] Discussion An exploratory program was initiated to evaluate the feasibility of applying additive manufacturing to the production of zirconium alloy components for light water reactor applications. The focus of the program was to demonstrate that zirconium alloy materials can be additively manufactured by characterizing their mechanical properties in the as-manufactured condition and after short-term irradiation. Additional work was conducted to identify options for improving the corrosion performance of the AM materials, which became the focus of this application.

[0121] The as-produced material had minimal chemical changes between the starting powder and the final material and was nearly 100% dense. The microstructure was martensitic and consisted of fine lath spacing resulting from rapid quenching from the melt. As expected, the texture was random with a texture parameter in three orthogonal directions close to 0.333. Room temperature tensile properties showed higher yield / ultimate stresses and lower elongations than conventionally processed Zircaloy-2 in the recrystallized condition. The increased strength is likely due to the martensitic microstructure, as well as the higher oxygen content in the additive-produced material (1700 wPPM vs. 1200 wPPM). At 573 K, a higher ultimate stress was also observed. These mechanical properties are consistent with the higher hardness of the additive-produced material. The hardness was also isotropic, consistent with a random structure.Finally, the yield stress and ultimate stress increased and the elongation decreased as the irradiation dose increased from 0 to 0.9 to 1.6 dpa.

[0122] Since additive manufacturing is intended to produce final-size parts without further mechanical deformation, annealing is the only option for post-processing. After removing the EDM recast layer from the surface, the coupons were annealed high in the alpha phase region for the purpose of nucleation and growth of SPPs.

[0123] The annealing parameter (A) was previously developed to characterize the heat treatment of materials following beta quenching [19,20,21,22]. A = te ( -Q / RT ) however, t = annealing time, h T = annealing temperature K Q = activation energy, and R=molar gas constant

[0124] The target A parameters for PWR (Zircaloy-4) and BWR (Zircaloy-2) applications are shown in Table 8. [Table 8]

[0125] Since this was an exploratory study, a high annealing temperature in the alpha temperature range (1033 K) and a reasonable process time (2 hours) were selected for the additively manufactured Zircaloy-2 material. The A parameters for this anneal are shown in Table 8 and compared to the target A parameters for PWR and BWR applications. The additive manufacturing anneal is closer to the PWR target and an order of magnitude higher than the BWR target. This comparison is provided only as a rough assessment of the potential impact of annealing on SPP since annealing a martensitic (additively manufactured) structure is significantly different from conventionally processed materials.

[0126] The result of annealing was a recrystallized microstructure and a notable improvement in short-term steam corrosion (compare Figures 8A-8B and 9A-9B). The recrystallized microstructure (see Figures 9A and 9B) is bimodal with both large and small alpha grains. Previous studies have shown such microstructures with exaggerated grain growth following small plastic deformations (e.g., 3% to 10%) [23, 24]. Unlike previous experience, the additively manufactured material was not deformed prior to annealing. Apparently, the large stresses in the material from rapid solidification and cooling to a martensitic microstructure provided the driving force for recrystallization.

[0127] Recrystallization of additively manufactured materials followed by a high temperature alpha anneal provides the following performance advantages: Short-term water vapor corrosion weight gain was comparable to conventionally processed materials, suggesting that adequate in-furnace corrosion resistance of additively manufactured materials is achievable. It was speculated that the recrystallized additively engineered microstructure would have a random texture given the random texture in the martensite additively engineered material. A random texture should result in minimal in-reactor irradiation growth.

[0128] These experiments demonstrated the feasibility of applying additive manufacturing to the production of zirconium alloy components. An approach to achieve adequate corrosion resistance in zirconium alloys is provided, along with the possibility of minimizing irradiation-induced growth.

[0129] conclusion

[0130] Zircaloy-2 block material was successfully fabricated from Zircaloy-2 powder by laser powder bed fusion. The experiments used the laser powder bed fusion method of additive manufacturing, but other additive manufacturing methods, especially those suitable for use with metals and metal alloys, can be substituted. Near perfect density (99.9%) was achieved, with small porosity consisting of spherical and irregularly shaped voids. Only minor changes in material chemistry between powder and block were observed.

[0131] Nitrogen content is higher in additive manufactured (85 PPM) than in conventional Zircaloy-2 material (22 PPM) and is reduced in the powder (110 PPM).

[0132] The bulk hydrogen in the as-prepared additively manufactured Zircaloy-2 block was higher (33 PPM) than that in the conventional ATI plate (4 PPM). Reduction of hydrogen in the starting powders may be beneficial.

[0133] The crystal structure of the additively manufactured block material was isotropic. The hardness was also isotropic, consistent with a random structure.

[0134] The microstructure of the additively produced Zircaloy-2 was beta-quenched with fine alpha phase laths, consistent with rapid quenching from the melt.

[0135] Limited efforts were made to evaluate the effect of annealing on corrosion in additively manufactured Zircaloy-2. A high annealing temperature was chosen in the alpha temperature range. Annealing resulted in a recrystallized microstructure and a significant improvement in short-term steam corrosion. The large stresses in the material from rapid solidification to a martensitic microstructure aid in the recrystallization of the additively manufactured material.

[0136] Various aspects of specific non-limiting embodiments of the invention encompassed by this disclosure include, but are not limited to, those listed in the following numbered paragraphs: A method for additively manufacturing a component for use in a nuclear reactor, the method comprising: 1. Additively manufacturing a component for use in a nuclear reactor utilizing a feedstock comprising a metal, and annealing the additively manufactured component at a first annealing temperature within an alpha phase temperature range, an alpha+beta phase temperature range of the metal, or a combination thereof. 2. The method of claim 1, wherein the first annealing temperature is within the alpha phase temperature range of the metal, and the method further comprises annealing the additively produced component for a second time at a second annealing temperature within the alpha + beta phase temperature range of the metal. 3. The method according to any one of items 1 to 2, wherein the metal comprises a zirconium alloy. 4. The method of any one of paragraphs 1 to 3, wherein the metal comprises Zircaloy-2, Zircaloy-4, HiFi™, a binary zirconium alloy, or a non-binary zirconium alloy containing tin and another alloying element, or a combination thereof. 5. The method of any one of paragraphs 1 to 3, wherein the metal comprises ZIRLO, optimized ZIRLO, AXIOM, a binary zirconium alloy containing niobium, or a non-binary zirconium alloy containing niobium and another alloying element, or a combination thereof. 6. The method of any one of claims 1 to 5, further comprising annealing the additively manufactured part for a second time at a second annealing temperature lower than the first annealing temperature. 7. The method of any one of claims 1 to 6, wherein the feedstock comprises a powder, a sheet, or a wire, or a combination thereof. 8. The method according to items 1 to 3 and 5 to 7, wherein the metal comprises a zirconium alloy containing niobium, the first annealing temperature is in the range of 600°C to 800°C, and the second annealing temperature is in the range of 450°C to 600°C. 9. The method according to item 8, wherein the second annealing temperature is in the range of 530°C to 580°C. 10. The method of any one of claims 1 to 9, wherein the first annealing temperature recrystallizes the microstructure of the additively manufactured component. 11. The method of claim 10, wherein the metal comprises an alloy including a matrix of a first phase metal and a second phase metal, and the second annealing temperature achieves a composition and size distribution of the second phase metal suitable for use in a nuclear reactor. 12. The method of any one of claims 1 to 11, wherein the additive manufacturing process comprises powder bed fusion, vat photopolymerization, binder jetting, material extrusion, directed energy deposition, material jetting, or sheet lamination, or a combination thereof. 13. A method for additively manufacturing a component for use in a nuclear reactor, comprising: depositing a layer of powder feedstock comprising a zirconium alloy across a build plate; and fastening at least selected regions of the layers together at the selected regions, the fastening comprising: rastering a laser across the layer of powder feedstock along a path guided by a pre-entered computer-aided design file of specifications for building a three-dimensional component; fusing the powder feedstock in the layer with a laser; solidifying the molten powder; Repeated fixing and gluing to provide an additively manufactured part; removing the additively manufactured part from the build plate; annealing the additively manufactured part at an annealing temperature within the alpha phase temperature range of the metal, the alpha-beta phase temperature range of the metal, or a combination thereof. 14. The method of claim 13, wherein the metal comprises Zircaloy-2, Zircaloy-4, HiFi™, a non-binary zirconium alloy containing tin and another alloying element, ZIRLO, ZIRLO Optimized, AXIOM, a binary zirconium alloy containing niobium, or a non-binary zirconium alloy containing niobium and another alloying element, or a combination thereof. 15. The method according to any one of items 13 to 14, wherein the annealing temperature is within the range of 450°C to 800°C. 16. The method according to any one of items 13 to 15, wherein the alloy comprises a zirconium alloy containing niobium, and the annealing temperature is within the range of 450°C to 620°C. 17. The method according to any one of items 13 to 16, wherein the annealing is carried out for a time period ranging from 0.1 hours to 100 hours. 18. The method of any one of claims 13 to 17, wherein the component comprises a debris filter, an intermediate flow mixer, a spacer grid, or a combination thereof. 19. The method of any one of claims 13 to 18, wherein the powder feedstock comprises an average particle size in the range of 10 micrometers to 100 micrometers. 20. The method according to any one of items 13 to 15 and 17 to 19, wherein the annealing temperature is in the range of 740°C to 780°C, and the annealing is carried out for a time period in the range of 1 hour to 3 hours.

[0137] All patents, patent applications, publications, or other disclosure materials mentioned herein are incorporated herein by reference in their entirety, as if each individual reference were expressly incorporated by reference. All references and any material, or portions thereof, that are said to be incorporated herein by reference are incorporated herein only to the extent that the incorporated material does not contradict existing definitions, statements, or other disclosure materials set forth in this disclosure. Thus, to the extent necessary, the disclosure set forth herein supersedes any conflicting material incorporated herein by reference, and the disclosure expressly set forth in the control of this application.

[0138] The present invention has been described with reference to various exemplary and illustrative embodiments. The embodiments described herein are understood to provide illustrative features of various details of various embodiments of the disclosed invention, and therefore, unless otherwise specified, it should be understood that, to the extent possible, one or more features, elements, parts, components, structures, modules, and / or aspects of the disclosed embodiments may be combined, separated, interchanged, and / or rearranged with one or more other features, elements, parts, components, structures, modules, and / or aspects of the disclosed embodiments without departing from the scope of the disclosed invention. Thus, it will be appreciated by those skilled in the art that various substitutions, modifications, or combinations of any of the exemplary embodiments may be made without departing from the scope of the invention. Moreover, those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the various embodiments of the invention described herein upon reviewing this specification. Thus, the present invention is not limited by the description of the various embodiments, but rather by the scope of the claims. quotation [1] JH Schemel, “ASTM Manual on Zirconium and Hafnium.” ASTM STP 639, American Society for Testing and Materials, Philadelphia, 1977. [2] Sahasrabudhe, H. and Bandyopadhyay, A. “Laser-Based Additive Manufacturing of Zirconium,” Appl. Sci. 2018, 8, 393; doi: 10.3390 / app8030393. [3] Dahlback, M., Limback, M., Hallstadius, L., Barberis, P., Burnel, G., Simonot, C., Andersson, T., Askeljung, P., Flygare, J., Lehtinen, B., and Massih, A. R., “The Effect of Beta-Quenching in Final Dimension on the Irradiation Growth of Tubes and Channels.” Zirconium in the Nuclear Industry: Fourteenth International Symposium, STP 1467, B. Kammenzind and P. Rudling Eds., ASTM International, West Conshohocken, PA, 2005, pp. 276-304. [4] Walters, L., Douglas, S. R., and Griffiths, M. “Equivalent Radiation Damage in Zirconium Irradiated in Various Reactors,” Zirconium in the Nuclear Industry: Eighteenth International Symposium, STP 1597. R. J. Comstock and A. T. Motta Eds., ASTM International, West Conshohocken, PA, 2018, pp. 676-690. [5] Standard Test Method for Density of Powder Metallurgy (PM) Materials Containing Less Than Two Percent Porosity, ASTM B311 -17 (2017) (West Conshohocken, PA: ASTM International, approved Apr. 1, 2017). [6] Standard Specification for Zirconium and Zirconium Alloy Sheet, Strip, and Plate for Nuclear Applications, ASTM B352 / B352M - 17 (2017) (West Conshohocken, PA: ASTM International, approved May 1, 2017). [7] Standard Test Method for Preparing Quantitative Pole Figures, ASTM E81 - 96 (2017) (West Conshohocken, PA: ASTM International, approved June 1, 2017). [8] Gale, B. and Griffiths, “Influence of Instrumental Aberrations on the Shultz Technique for the Measurement of Pole Figures,” Brit. J. Appl. Phys., 11, 96-102, (1960). [9] “popLA, Preferred Orientation Package - Los Alamos,” Software Manual by S. I. Wright and U. F. Kocks, Los Alamos National Laboratory, Los Alamos, NM

[10] Standard Test Method for Microindentation Hardness of Materials, ASTM E384 - 17 (2017) (West Conshohocken, PA: ASTM International, approved June 1, 2017).

[11] Standard Test Methods for Tension Testing of Metallic Materials, ASTM E8 / E8M - 16a (2016) (West Conshohocken, PA: ASTM International, approved Aug. 1, 2016).

[12] Standard Test Methods for Elevated Temperature Tension Tests of Metallic Materials, ASTM E21 - 17 (2017) (West Conshohocken, PA: ASTM International, approved Dec. 1, 2017).

[13] Standard Test Method for Corrosion Testing of Products of Zirconium, Hafnium, and Their Alloys in Water at 680°F(360℃) or in Steam at 750°F (400℃), ASTM G2 / G2M -19 (2019) (West Conshohocken, PA: ASTM International, approved Jan. 1, 2019).

[14] Massih, A. R., Andersson, T., Witt, P., Dahlback, M., and Limback, M., “Effect of Quenching Rate on β-α Phase Transformation Structure in Zirconium Alloys,” Journal of Nuclear Materials, Vol. 322, 2003, pp. 138-151.

[15] Morize, P., Baicry, J., and Mardon, J. P., “Effect of Irradiation at 588 K on Mechanical Properties and Deformation Behavior of Zirconium Alloy Strip,” Zirconium in the Nuclear Industry: Seventh International Symposium, ASTM STP 939, R. B. Adamson and L. F. P. Van Swam, Eds., American Society for Testing and Materials, Philadelphia, 1987, pp. 101-119.

[16] Charquet, D. and Alheritiere, E., “Influence of Impurities and Temperature on the Microstructure of Zircaloy-2 and Zircaloy-4 after Beta Alpha Phase Transformation,”Zirconium in the Nuclear Industry: Seventh International Symposium, ASTM STP 939, R. B. Adamson and L. F. P. Van Swam, Eds., American Society for Testing and Materials, Philadelphia, 1987, pp. 284-291.

[17] Garzarolli, F., Stehle, H., Steinberg, E., and Weidinger, H., “Progress in the Knowledge of Nodular Corrosion,” Zirconium in the Nuclear Industry: Seventh International Symposium, ASTM STP 939, R. B. Adamson and L. F. P. Van Swam, Eds., American Society for Testing and Materials, Philadelphia, 1987, pp. 417-430.

[18] C. L. Whitmarsh, “Review of Zircaloy-2 and Zircaloy-4 Properties Relevant to N. S. Savannah Reactor Design” ORNL Report ORNL-3281; UC-80-Reactor Technology, TID-4500 (17 th ed.) Tennessee, 1962.

[19] Steinberg, E., Weidinger, H. G., and Schaa, A., “Analytical Approaches and Experimental Verification to Describe the Influence of Cold Work and Heat Treatment on the Mechanical Properties of Zircaloy Cladding Tubes,” Zirconium in the Nuclear Industry: Sixth International Symposium, ASTM STP 824, D. G. Franklin and R. B. Adamson, Eds., American Society for Testing and Materials, 1984, pp. 106-122.

[20] Garzarolli, G., Steinberg, E., and Weidinger, H. G., “Microstructure and Corrosion Studies for Optimized PWR and BWR Zircaloy Cladding,” Zirconium in the Nuclear Industry: Eighth International Symposium, ASTM STP 1023, L. F. P. Van Swam and C. M. Eucken, Eds., American Society for Testing and Materials, Philadelphia, 1989, pp. 202-212.

[21] Tagstrom, P., et al., "Effects of Hydrogen Pickup and Second-Phase Particle Dissolution on the In-Reactor Corrosion Performance of BWR Claddings," Zirconium in the Nuclear Industry: Thirteenth International Symposium, ASTM STP 1423, G. D. Moan and P. Rudling, Eds., ASTM International, West Conshohocken, PA, 2002, pp. 96-118.

[22] Romero J., et al., “Evolution of Westinghouse fuel cladding”, in Proceedings of International Conference on Light Water Reactor Fuel Performance (Top Fuel 2014), Paper 100019. La Grange Park, IL: ANS, 2014.

[23] Tong, V. S. and T. B. Britton, “Formation of very large ‘blocky alpha’ grains in Zircaloy-4”, Acta Materialia, 129 (2017) 510-520.

[24] D. F. Washburn, “The formation of large grains in alpha Zircaloy-4 during heat treatment after small plastic deformations,” Knolls Atomic Power Laboratory, General Electric Company, Report KAPL-3062, New York, 1964.

Claims

1. 1. A method for additively manufacturing a component for use in a nuclear reactor, comprising: additively manufacturing said component utilizing a metal-containing feedstock; annealing the additively manufactured component at a first annealing temperature within the alpha phase temperature range of the metal, the alpha+beta phase temperature range of the metal, or a combination thereof; the metal comprises a zirconium alloy, the zirconium alloy comprising less than 3 wt. % of one or more alloying elements based on the total weight, the one or more alloying elements comprising tin, chromium, iron, nickel, copper, or vanadium, or any combination thereof; The method of claim 1, wherein the annealing recrystallizes the microstructure of the additively manufactured component.

2. the first annealing temperature is within the alpha phase temperature range of the metal; 10. The method of claim 1, further comprising annealing the additively manufactured component for a second time at a second annealing temperature within the alpha + beta phase temperature range of the metal.

3. 3. The method of claim 1 or 2, wherein the metal comprises Zircaloy-2, Zircaloy-4, a zirconium alloy containing 0.4 wt.% tin based on the total weight, a binary zirconium alloy, or a non-binary zirconium alloy containing tin and another alloying element, or a combination thereof.

4. 4. The method of any of claims 1 to 3, wherein the metal comprises a binary zirconium alloy containing niobium, or a non-binary zirconium alloy containing 0.6 wt.% to 1.1 wt.% tin, 0.8 wt.% to 1.2 wt.% niobium, and 0.09 wt.% to 0.13 wt.% iron, based on the total weight, or a combination thereof.

5. The method of any of claims 1 to 4, further comprising annealing the additively manufactured component for a second time at a second annealing temperature lower than the first annealing temperature.

6. The method of any of claims 1 to 5, wherein the feedstock comprises a powder, a sheet, or a wire, or a combination thereof.

7. 6. The method of claim 5, wherein the metal comprises a zirconium alloy with niobium, the first annealing temperature is in the range of 600°C to 800°C, and the second annealing temperature is in the range of 450°C to 600°C.

8. The method of claim 7, wherein the second annealing temperature is in the range of 530°C to 580°C.

9. 10. The method of claim 8, wherein the metal comprises an alloy including a matrix of a first phase metal and a second phase metal, and the second annealing temperature achieves a composition and size distribution of the second phase metal suitable for use in a nuclear reactor.

10. The method of any of claims 1 to 9, wherein the additive manufacturing comprises powder bed fusion, vat photopolymerization, binder jetting, material extrusion, directed energy deposition, material jetting, or sheet lamination, or a combination thereof.

11. 1. A method for additively manufacturing a component for use in a nuclear reactor, comprising: depositing a layer of powder feedstock of a metal comprising a zirconium alloy across a build plate; and securing at least selected areas of the layers together at the selected areas; The fixing comprises: rastering a laser across the layer of powder feedstock along a path guided by a computer-aided design file pre-populated with specifications for the three-dimensional component to be built; fusing the powder feedstock in the layer with a laser; and solidifying the molten powder; The method further comprises: repeating the depositing and applying to provide the additively manufactured component; and removing the additively manufactured component from the build plate; annealing the additively manufactured component at an annealing temperature within the alpha phase temperature range of the metal, the alpha-beta phase temperature range of the metal, or a combination thereof; the zirconium alloy comprising less than 3 wt. % of one or more alloying elements based on the total weight, the one or more alloying elements comprising tin, chromium, iron, nickel, copper, or vanadium, or any combination thereof; The method of claim 1, wherein the annealing recrystallizes the microstructure of the additively manufactured component.

12. 12. The method of claim 11, wherein the metal comprises Zircaloy-2, Zircaloy-4, a zirconium alloy containing 0.4 wt.% tin based on the total weight, a binary zirconium alloy containing tin, a non-binary zirconium alloy containing tin and another alloying element, a binary zirconium alloy containing niobium, or a non-binary zirconium alloy containing 0.6 wt.% to 1.1 wt.% tin, 0.8 wt.% to 1.2 wt.% niobium, and 0.09 wt.% to 0.13 wt.% iron based on the total weight, or a combination thereof.

13. The method according to claim 11 or 12, wherein the annealing temperature is in the range of 450°C to 800°C.

14. The method of any of claims 11 to 13, wherein the zirconium alloy comprises a zirconium alloy containing niobium, and the annealing temperature is in the range of 450°C to 620°C.

15. The method of any of claims 11 to 14, wherein the annealing occurs for a time in the range of 0.1 hours to 100 hours.

16. The method of any of claims 11 to 15, wherein the component comprises a debris filter, an intermediate flow mixer, a spacer grid, or a combination thereof.

17. The method of any of claims 11 to 16, wherein the powder feedstock comprises an average particle size in the range of 10 micrometers to 100 micrometers.

18. A method according to any of claims 11 to 17, wherein the annealing temperature is in the range of 740°C to 780°C and the annealing occurs for a period in the range of 1 hour to 3 hours.

Citation Information

Patent Citations

  • Manufacture of high-ductility and highly corrosion-resistant zirconium-base alloy member and the member

    JP1987182258A

  • Zirconium-based alloy tubes for nuclear reactor fuel assemblies and process for making such tubes

    JP1998513262A

  • Process for producing flat articles made of zirconium alloys, products obtained by said process and fuel assembly elements for nuclear power plant reactors made from said flat articles

    JP2007500788A

  • Zirconium alloy resistant to shadow corrosion for components of boiling water reactor nuclear fuel assemblies, components made of the alloy, nuclear fuel assemblies, and their use

    JP2010511165A

  • Method for manufacturing parts made of metal alloy with amorphous phase

    JP2017528604A